2020
DOI: 10.1002/dvdy.252
|View full text |Cite
|
Sign up to set email alerts
|

Phosphosite T674A mutation in kinesin family member 3A fails to reproduce tissue and ciliary defects characteristic of CILK1 loss of function

Abstract: Background Kinesin family member 3A (KIF3A) is a molecular motor protein in the heterotrimeric kinesin‐2 complex that drives anterograde intraflagellar transport. This process plays a pivotal role in both biogenesis and maintenance of the primary cilium that supports tissue development. Ciliogenesis associated kinase 1 (CILK1) phosphorylates human KIF3A at Thr672. CILK1 loss of function causes ciliopathies that manifest profound and multiplex developmental defects, including hydrocephalus, polydactyly, shorten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…A key phosphorylation target of RCK is heterotrimeric kinesin-2: in mammals KIF3A [ 58 , 79 ] and in Chlamydomonas FLA8, the homolog of KIF3B [ 177 ]. In mice, KIF3A has been shown to be not the only target of CILK1, since mutants expressing a non-phosphorylatable KIF3A variant have a distinct phenotype from CILK1-knockouts [ 178 ]. The phenotypes of the RCK-knockouts in different organisms–(tip) accumulation of IFT components– resemble those of dynein-2 and IFT-A knockouts [ 11 , 179 , 180 , 181 , 182 ].…”
Section: Ift Regulation From the Perspective Of Regulatory Proteinsmentioning
confidence: 99%
“…A key phosphorylation target of RCK is heterotrimeric kinesin-2: in mammals KIF3A [ 58 , 79 ] and in Chlamydomonas FLA8, the homolog of KIF3B [ 177 ]. In mice, KIF3A has been shown to be not the only target of CILK1, since mutants expressing a non-phosphorylatable KIF3A variant have a distinct phenotype from CILK1-knockouts [ 178 ]. The phenotypes of the RCK-knockouts in different organisms–(tip) accumulation of IFT components– resemble those of dynein-2 and IFT-A knockouts [ 11 , 179 , 180 , 181 , 182 ].…”
Section: Ift Regulation From the Perspective Of Regulatory Proteinsmentioning
confidence: 99%
“…Mutations in the ICK gene in humans cause ciliopathies [34][35][36], and knockout (KO) and mutant Ick mice manifest ciliopathy phenotypes [32,37,38]. Previous studies proposed that the phosphorylation of KIF3A, a kinesin-II subunit, by ICK is crucial for the regulation of ciliary protein trafficking [32,39]; however, a recent study suggested that KIF3A phosphorylation is dispensable for ciliary function [40].…”
Section: Introductionmentioning
confidence: 99%
“…Both KIF3A and GSK3β have been linked to intraflagellar transport and cilia length control [ 32 , 33 ]. However, our prior study showed that deficiency in CILK1 phosphorylation of KIF3A alone is insufficient to account for the cilia phenotype caused by CILK1 inactivation [ 34 ]. Therefore, it remains a mystery as to which CILK1 substrate(s) mediate the effect of Alvocidib in the regulation of intraflagellar transport and cilia length.…”
Section: Discussionmentioning
confidence: 99%